Predictive value of uterine artery: peak systolic velocity on the day of trigger for clinical pregnancy rate in infertile women - Makhija, Karishma; Shrivasatava, Deepti; Tiwari, M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The purpose of the study is to evaluate the role of uterine artery blood flow parameter measured by uterine artery two-dimensional (2D) power coloured doppler (PCD) ultrasound in predicting fertility outcomes in women undergoing ART treatment. Methods: It is prospective observational study. Total of 60 patients were included of receiving infertility treatment in the age group20-40 years. 20 patients were selected for timed intercourse , 20 patients were selected for intrauterine insemination , 20 patients were selected for invitro fertilization. Transvaginalsonography will be done on the day of trigger by BHCG , UA PSV were measured, and endometrial blood flow will be assessed. Predictivity of pregnancy rate will be looked after by 3 ways: BHCG values , UPT, Gestational sac on USG. Results: In TI/IUI/IVF cycles the Doppler parameter PSV of uterine artery (23.08+/-3.39 vs 20.37-/+5.43) in pregnant vs non-pregnant group did not differ significantly. The mean PSV of UA shows no significant difference women who were became pregnant during treatment and the women who were not became pregnant. Conclusions: With help of Doppler parameter imaging of women undergoing infertility it was found that UA PSV is non-significant to decide the prediction of pregnancy outcome.